MAZĀYĀ BILĀD AL-YAMAN WA AL-YAMĀNIYYŪN FI AL-HADĪTH: AL-DIRĀSAT AL-TĀRIKHIYYAT AL-IJTIMĀ’IYYAT - Sa’adah, Rifa Tsamrotus (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
This paper discusses the history of the country of Yemen which is located in the western Arabian Peninsula. The safe country has an unique history and is recognized as a country that has been colored by civilization and science in the past. In addition, Yemen has the privilege of having the editorial Nafs al-Rahman, defined as the soul of God mentioned in the history of al-Thabrani in his Musnad al-Syamiyyin’s book. The editor is Inni Ajidu Nafasa Rabbakum Min Qibali al-Yaman. In addition, there are several sources of verses of the Koran that allude to the state of Yemen which includes the stories of the Yemeni people who occupied the country of Yemen. This study reveals that the state of Yemen had many virtues since the time of the Prophets, before and after the advent of Islam. The country of Yemen is known as the nation of the Arabian Peninsula that is happy, beautiful, and full of fruits or vegetables, and much more. Therefore, this study specifically discusses the Yemeni state and its people from all aspects and their influence on Islam which will be presented in the study of socio-historical methods.